2015
DOI: 10.1080/14636778.2015.1034849
|View full text |Cite
|
Sign up to set email alerts
|

Metaphors in search of a target: the curious case of epigenetics

Abstract: Carrying out research in genetics and genomics and communicating about them would not be possible without metaphors such as “information,” “code,” “letter” or “book.” Genetic and genomic metaphors have remained relatively stable for a long time but are now beginning to shift in the context of synthetic biology and epigenetics. This article charts the emergence of metaphors in the context of epigenetics, first through collecting some examples of metaphors in scientific and popular writing and second through a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 42 publications
0
49
0
9
Order By: Relevance
“…Scholars have suggested that genes should be understood in more "contextual" manner, which would acknowledge that they interact with their biological, environmental and social context (Kay, 2000). Recent metaphors of genes as music or as part of an ecology identified in scientific and media coverage of epigenetics and the Human Microbiome (Nerlich & Hellsten, 2009;Stelmach & Nerlich, 2015) suggest that more interactive notions of genes are emerging. The way in which the ontological metaphor of big data was articulated on 23andMe's website and media coverage did not, however, suggest that genes are influenced by other factors, even if other factors were acknowledged to play a role in determining wellness and illness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scholars have suggested that genes should be understood in more "contextual" manner, which would acknowledge that they interact with their biological, environmental and social context (Kay, 2000). Recent metaphors of genes as music or as part of an ecology identified in scientific and media coverage of epigenetics and the Human Microbiome (Nerlich & Hellsten, 2009;Stelmach & Nerlich, 2015) suggest that more interactive notions of genes are emerging. The way in which the ontological metaphor of big data was articulated on 23andMe's website and media coverage did not, however, suggest that genes are influenced by other factors, even if other factors were acknowledged to play a role in determining wellness and illness.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the metaphor of information insinuated that there was one accurate expert interpretation of genes, the metaphor of big data cast DNA as open for multiple interpretations or to be "played" or "brought into life" differently. The musical metaphor of "playing" DNA differently has been observed to be used in epigenetics (Stelmach & Nerlich, 2015), however, in this instance it was not nature or environmental triggers but software that was "playing" DNA differently; the latter metaphor implied that data was dead or inert until it was brought to life by software, further imputed it with powers of vitality and creativity.…”
Section: Multiple Interpretationsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, low birth weight came to be seen as resulting from genes rather than poor nutrition and prenatal healthcare, illustrating how geneticization is also frequently coupled with individualistic notions of health and illness, downplaying social and environmental causes and solutions. Deterministic metaphors for genes, such as "blueprint" or "book of life," analyzed also on the pages of this journal (Nelkin 1994;Nerlich and Hellsten 2004) have proved enduring in popular and scientific media, even if new scientific approaches, such as epigenetics, have generated new metaphors, such as genes as musical scores that can be played differently (Stelmach and Nerlich 2015). Analyses of the websites of DTCGT companies have noted that they represent genes in deterministic fashion (Nordgren and Juengst 2009) and foster the neoliberal notion of health as an individual responsibility (Harvey 2010).…”
Section: Geneticization: Past and Presentmentioning
confidence: 99%
“…"the genetic program", "biological clock") are now used as conventional terms, others are produced in ways that align with the new topics, concepts and mechanisms (Semino, 2008). Their semantic ambiguity makes metaphors especially useful as scientists often communicate about obscure entities and processes about which little is yet known (Keller, 2002, Journet, 2010, Stelmach & Nerlich, 2015.…”
Section: Introductionmentioning
confidence: 99%